Licenciados em sociologia e mercado de trabalho na transição do milénio - Gonçalves, Carlos Manuel (2004)
To reflect, nowadays, about the Portugals' sociology situation implies to take into account, among other aspects, the Sociologists' rhythms, ways and conditions of transition and prevalence in the labour market. It is intended, in this article, to develop this theme with the analysis of the transition processes to the labour market by the Faculdade de Letras da Universidade do Porto graduated in Sociology. Assuming a comparative perspective with the previous study developed by the authors about the same issue, it will be analyzed the profissional dimension of the referred graduates, in particular of those that identify themselves as sociologists.